FACTORS AFFECTING SUCCESS IMPLEMENTATION OF ELECTRNIC GOVERNMENT IN SAUDI ARABIA - Maher Mohammad Aseeri, 1985-, author; Rusni Daruis, Assoc.Prof., supervisor; Faculty of Advanced Informatics School (Kuala Lumpur : Universiti Teknologi Malaysia, 2014)
Thesis